Gentamicin alters Akt-expression and its activation in the guinea pig cochlea. (17th December 2015) - Heinrich, U.-R.; Strieth, S.; Schmidtmann, I.; Li, H.; Helling, K.
Graphical abstract: Highlights: Gentamicin-induced hearing loss was paralleled by increased Akt-expression in organ of Corti and spiral ganglion cells. Gentamicin-dependent increase in Akt-activation was restricted exclusively to spiral ganglion cells. Correlations between Akt- and p-Akt-expression were found in the stria vascularis and in the interdental cells. Correlations between interdental cells, nerve fibers and spiral ligament were identified for the Akt/p-Akt ratios. Abstract: Gentamicin treatment induces hair cell death or survival in the inner ear. Besides the well-known toxic effects, the phosphatidylinositol-3 kinase/Akt (PI3K/Akt) pathway was found to be involved in cell protection. After gentamicin application, the spatiotemporal expression patterns of Akt and its activated form (p-Akt) were determined in male guinea pigs. A single dose of 0.1 mL gentamicin (4 mg/ear/animal) was intratympanically injected. The auditory brainstem responses (ABRs) were recorded prior to application and 1, 2 and 7 days afterward. At these three time points the cochleae ( n  = 10 in each case) were removed, transferred to fixative and embedded in paraffin. Seven ears were used as untreated controls. Gentamicin, Akt and p-Akt were identified immunohistochemically in various regions of the cochlea and their staining intensities were quantified on sections using digital image analysis. The application of gentamicin resulted in hearing loss with a concomitant up-regulation of Akt-expression in the organ of Corti and spiral ganglion cells and an additional activation in spiral ganglion cells. At the level of individual ears, clear intracellular correlations were found between Akt- and p-Akt-expression in the stria vascularis and interdental cells and, to a minor extent, in the spiral ligament and the organ of Corti. Furthermore, statistical evidence for the connection between gentamicin up-take and hearing loss was detected. The increase in Akt- and p-Akt-expression in the organ of Corti and spiral ganglion cells indicates a selected response of the cochlea against gentamicin toxicity.